Associations between childhood body size and seventeen adverse outcomes: analysis of 65, 057 European women. Issue 1 (December 2017) - Li, Jingmei; Eriksson, Mikael; He, Wei; Hall, Per; Czene, Kamila
Abstract Large childhood body size has been consistently shown to be associated with decreased breast cancer risk. However, it is important to consider the effects of a large childhood body size on other adult diseases. It is not clear if the associations between childhood body size and adult diseases will persist if they later attain healthy weight. The associations between body size at age 7 and 17 adverse outcomes in adulthood were examined using Cox models in a Swedish study of 65, 057 women. Large body size at age 7, when compared to small body size, was associated with decreased risk for breast cancer (HR [95% CI]: 0.81 [0.70–0.93]) and increased risks for anorexia (2.13 [1.63–2.77]) and bulimia (1.91 [1.35–2.70]). Neither adjusting for adult BMI nor restricting the dataset to lean adults (BMI < 25 kg/m2 ) attenuated the associations. While large body size at age 7 by itself was positively associated with increased risks of diabetes (1.34 [1.16–1.55]), PCOS (1.69 [1.13–2.51]) and hypertension (before age 60), the associations were no longer significant after controlling for adult BMI. No clear associations were found with the remaining adverse outcomes (cervical, uterine, melanoma, colon cancer, depression, ovarian cyst, stroke, hyperlipidemia, heart failure, myocardial infarction, and angina pectoris).